PERSEPSI KONSUMEN PADA OLEH OLEH KHAS MANADO DI TOKO MIENS SOUVENIR - Umboh, Junita Fiane; Pangemanan, Paulus Adrian; Manginsela, Elsje Pauline (Sam Ratulangi University, 2022)
This study aims to determine and examine consumer perceptions of typical Manado at Miens Souvenir during the pandemic Covid-19. The study was conducted from September 2020 to May 2021. The data used in this study is primary data, namely data collection through media online with a google form to respondents who have shopped for souvenirs typical of Manado with 30 samples of respondents. Secondary data were obtained owners from Miens Souvenir and literature related to this research. The research data were analyzed using descriptive analysis based on the Likert Scale. The results showed that from the attributes of shopping convenience, product, price, physical place of business, and service quality to the five factors that tended to influence it, they were included in the category of strongly agree (41.1%), agree (47.0%), neutral (10.2%), disagree (0.5%), while strongly disagree (1.0%). From the category of strongly agree, the ease of shopping attribute ranks first (46.7%), followed by service attributes (43.2%), price attributes (41.0%), product attributes (38.4%), and final position attributes physical place of business (36.2%).